Seismic behaviour of reinforced concrete buildings: Impact of inter-story pounding with adjacent structures on one and both sides - Borekci, Muzaffer; Dag, Birkan; Eroglu, Abdulhamit (ELSEVIER SCIENCE INC, 2024)
In metropolitan areas with large populations, buildings are often constructed adjacent to each other with insufficient gaps which leads to potential collisions during seismic events may cause damage to structural elements. Therefore, it is crucial to assess the seismic behaviour of buildings subjected to the pounding effect. While existing studies in the literature have primarily focused on floor-to-floor pounding between two adjacent buildings, inter-story pounding between adjacent buildings with different story heights is another important situation. This phenomenon results in large shear forces in the pounded columns due to the slabs of the adjacent building. Additionally, pounding studies generally focus on the mechanics of one-sided collisions, while studies on pounding between three or more buildings have been relatively fewer despite its increasing prevalence in metropolitan areas. For these reasons, the evaluation is extended by this study to inter-story pounding between buildings adjacent on one side and both sides. To achieve this, 3-, 6-, and 10-story buildings were analytically modelled in SAP2000 for three distinct pounding scenarios: stand-alone, adjacent on one side, and adjacent on both sides and nonlinear time history analyses were performed using 11 pairs of ground motion records. For the analysis, stand-alone buildings were assumed to exhibit nonlinear behaviour, while adjacent buildings with the same number of stories but different story heights were assumed to be ductile and modelled with linear behaviour. The seismic behaviour of the focal nonlinear buildings due to pounding effects was assessed by comparing the plastic rotations and shear force responses of the structural elements. It is indicated in this study that inter-story pounding between two adjacent buildings does not significantly alter the plastic rotation enough to increase the damage state of beams and columns, regardless of the pounding scenario. Despite this, the collided columns are shown to experience an increase in shear force response due to inter-story pounding, leading to an exceedance of their corresponding shear force capacity and shear failure mechanism, especially when adjacent on both sides.
Keywords: Reinforced concrete buildings; Adjacent buildings; Inter-story pounding; Pounding in series; Collision; Nonlinear time history analysis; Seismic performance; MITIGATION MEASURES; MODEL; VIBRATION; DAMAGE; Engineering